The Judges Ethics and Justice: An Analysis of Law Enforcement in Indonesian Court System - Setyowati, Herning (Law Research Review Quarterly, 2021)
Technical skills education in the field of law that neglects the aspect relating to the responsibility of a person to the person entrusted to him and his profession in general and the values and ethical measures that should be guidelines in carrying out his profession will only produce skilled handyman in the field of law and his profession. Such circumstances not only make the clinical education incomplete because the prospective member of the profession does not know how he should use his acquired technical skills. In fact, it is no exaggeration to say that technical skills education without the education of professional and ethical responsibility is dangerous. In general, it can be said that every profession puts the expert concerned in a special circumstance, both because of the extraordinary powers entrusted to him (such as judges and prosecutors) as well as the fate of the interested person entrusted to him (in the case of the defense). When viewed in the framework of law enforcement as a matter of public interest, that responsibility is essentially also a trust mandate concerning public interest (public trust). It is undeniable that certain positions or professions have special positions or duties because they are subject to more severe conditions than are generally applicable for good practice rather than their duties or functions and the protection of those concerned.